Colonic Metastasis with Anemia Leading to a Diagnosis of Primary Lung Adenocarcinoma - Vasa Jevremovic; Amer Abboud; Stuart Krauss (Case Reports in Oncological Medicine)
Metastasis occurs with 50% of lung carcinomas, most commonly to lymph nodes, adrenal glands, liver, bone, and brain. It is extremely rare for lung cancer to present with symptoms of a gastrointestinal metastasis and even more so pertaining to the colon. To the best of our knowledge, only 12 such cases have been reported in the literature. We describe a case of a 71-year-old female presenting with refractory iron deficiency anemia that was found to have a lesion in the transverse colon. Pathology revealed adenocarcinoma of the lung and a subsequent lung lesion was discovered in a retrograde fashion.